A matter of quality: Kurt Goldstein‘s assessment of the abstract attitude after brain damage - Stefan Frisch; Alexandre Métraux (Arquivos de Neuro-Psiquiatria)
ABSTRACT Neurologist and psychiatrist Kurt Goldstein (1878-1965) made substantial contributions to neuropsychology in general and to the development of tests for the assessment of brain damage sequelae in particular. Unlike present-day neuropsychology’s psychometric orientation, Goldstein kept a critical distance to a mere quantitative evaluation. Eighty years ago, he impressively demonstrated his own, qualitatively oriented diagnostic approach both in a remarkable monograph and in a didactic film, in collaboration with psychologist Martin Scheerer (1900-1961). By modifying a classical paradigm for the assessment of deficits in visuospatial construction, the Block Design Test, the two authors developed the Goldstein-Scheerer Cube Test. This version characterizes itself by offering the patient different types of cues in order to reveal the nature of the deficit at stake. The test remains an impressive illustration of Goldstein’s most famous neuropsychological concept, viz. the human ability to abstract from a concrete situation: the abstract (or categorial) attitude.